Mighty pup power! ebook - Nickelodeon Publishing (PAW Patrol., 2020)
Nickelodeon's PAW Patrol become super pups after a mysterious meteorite crashes near Adventure Bay. But can Marshall, Chase, Skye, and the rest of the team stop Mayor Humdinger from getting powers and using them for his own sneaky purposes? Girls and boys ages 3 to 7 will find out in this all-new storybook. This Nickelodeon read-along contains audio narration.